Sequestered Disc Herniation in a Dog - Villanova Junior, José Ademar; Dipp, Guilherme; Silva Neto, Bruno Parbelini; Balardini, Janayna de Lima Maske; Eigio Isaka, Juliano José; de Oliveira Reusing, Mhayara Samile; Engracia Filho, Jair Rodini (Acta Scientiae Veterinariae, 2019)
Background: Dogs are frequently affected by intervertebral disc degeneration, a structural failure associated with changes accelerated by aging. Disc degeneration may occur in the presence or absence of clinical signs, which are variable and common to other spinal cord diseases and therefore early diagnosis is crucial to a successful outcome. Treatment may be conservative or surgical according to severity of the clinical signs and should be combined with a rehabilitation protocol. Prognosis depends on the location of the spinal cord compression, volume and velocity of the disc material herniation and time between initial clinical signs, definitive diagnosis and therapeutic approach. Case: A nonchondrodystrophic 14-year-old dog with acute clinical manifestation of paraparesis and proprioceptive deficit in hind limbs was submitted to myelography examination. There was contrast column deviation in the T13-L1 region, determining spinal compression, and spondyloses were also noted in several thoracolumbar vertebrae. Hemilaminectomy was performed with complete removal of the compressor fragment. Histological analysis confirmed the presence of fibrocartilaginous material that corresponds to the part of the annulus fibrosus. The kidnap of the fragment was characterized by loss of continuity with the remaining disk. In these cases, magnetic resonance imaging does provides the definitive diagnosis, since neoplasm, arachnoid cysts and abscesses may be remaining differential diagnosis. Therefore, surgical approach followed by histopathological analysis of the obtained material are necessary to confirm the diagnosis. Discussion: The present report differs from most cases of disc herniation because it is a thoracolumbar lesion with an acute manifestation of significant neurological deficit in an elderly dog of non-chondrodystophic breed. Also, material of the free fibrous annulus itself in the medullary canal is not a common histopathological presentation of disc extrusion usually composed by nucleus pulposus. After neurolocalization of the lesion by clinical neurological examination, the radiographic evaluation shall precedes the myelography, since this is contraindicated when there is suspicion of discoespondylitis, fracture, dislocation or vertebral subluxation, which had not yet been discarded. Even if the MRI is performed, in the cases of a sequestered fragment, it still remais differential diagnoses include arachnoid cysts, discoespondylitis, hematomas, abscesses and neoplasms, including metastases, so only surgical approach to obtain material for histopathological analysis may provide definitive diagnosis. According to the histopathological examination, the herniated material had a fibrocartilaginous characteristic: several concentric fibrous blades, composed of collagen and fibrocartilage, thus characterizing the herniated material as a fragment of the fibrous ring. When removed from the vertebral canal, the contents did not show resistance, being withdrawn completely and without continuity with its origin intervertebral disc. The patient’s disc herniation could not be classified as a disc protrusion because this affection is described as a projection of the fibrous annulus towards the vertebral canal due to the partial rupture of fibers and mineralization of the nucleus pulposus, without discontinuity of some content. Disc protrusion shows mild and progressive signs, except if there is complete rupture of the fibrous ring as can be seen in the sequestered disc herniation. Although infrequent, elderly animals of non-chondrodisiotic races may show acute signs of neurological deficits. Sequestrated disc herniation may mimic other lesions, requiring a surgical approach to obtain material for histopathological analysis to confirm the diagnosis.